Talking it Through: Responses to Sorcery and Witchcraft Beliefs and Practices in Melanesia - Forsyth, Miranda (ANU Press, 2015)
Sorcery and witchcraft practices and beliefs are pervasive across Melanesia. They are in part created by, and give rise to, a wide variety of poor social and developmental outcomes. These include uneven economic development, low public health, lack of social cohesion, crime, fear and insecurity. A further very visible problem is the attacks on men and women who are accused of being practitioners of witchcraft or sorcery, which can lead to serious bodily harm, banishment and sometimes death. Today, many communities, individuals, church organisations and policymakers in Melanesia and internationally are exploring ways to overcome the negative social outcomes associated with witchcraft and sorcery practices and beliefs. This book brings together a collection of chapters written by a diverse range of authors, both Melanesian and non-Melanesian, providing crucial insights both into how these practices and beliefs are playing out in contemporary Melanesia, and also the types of interventions that are being trialled or debated to address the problems associated with them.